Investigation the effect of cationic surfactant on heat transfer performance in heat exchanger - Abdul Haffizh, Zulkifli (2013)
Drag reducing surfactant fluids are known to suffer from heat transfer capabilities in recirculating system. In this experiment, the main purpose is to investigate the effect of cationic surfactant flow parameter on heat transfer performance in heat exchanger. In the present research, Cetyltrimethylammonium bromide (CTAB) was tested with concentration level of 500 ppm, 1000 ppm and 1500 ppm at 50ºC, 60 ºC and 70 ºC temperature for each concentration level. The experimental result showed that, temperature and concentration effect the heat transfer performance of the CTAB surfactant. At concentration of 1500 ppm, highest heat transfer obtained at temperature of 50ºC. The same results were obtained at temperature of 60ºC and 70ºC with corresponding concentration value of 500 ppm and 1000 ppm. The results also showed that the heat transfer rate with existing of UV light upon cationic surfactant flow enhance the heat transfer rate with 11% increase at 50°C with 1500 ppm, 6% increase at 60°C with 500 ppm and 5% increase at 70°C 1000.